Family doctors seen through the eyes of specialists: a qualitative study - Probst, Anna; Natanzon, Iris; Szecsenyi, Joachim; Joos, Stefanie (International journal of family medicine, 2013)
Germany is facing a shortage of young family doctors. In search of possible reasons the aim of this study was to explore the perception of specialists on family doctors. Within a qualitative study 16 medical specialists from different fields in hospital and outpatient care setting were interviewed. Interviews were analysed using qualitative content analysis according to Mayring. Most of the interviewed specialists have a positive view on family doctors although a certain depreciative assumption is resonated in a number of statements. According to the specialists, family doctors enjoy a high status in public, even if social processes of change may have a negative influence on their rather old-fashioned image. Specialists find that family medicine is underrepresented in university education suffering from an upgrading of specialized disciplines. Altogether the majority of the interviewed specialists certify family doctors in Germany a positive image. Lecturer in medical education and training should be aware of their key role in the career choices of young trainees and avoid degradation or upgrading of certain medical disciplines. Interlinked measures on different levels focusing on the improvement of working conditions and representation at the universities would be needed to regain attractiveness for the family doctor's profession as a career choice for young doctors.